3D printing of functional ceramics - Phoon, Kenneth Zhen Hao (2018)
In this final year project, the objectives were to study the viscosity of the silicon nitride ‘inks’ when different factors were varied and discover potentially suitable ‘inks’ that can be used in the 3D printer. Silicon Nitride (Si3N4) powders were used as the main material, PAA and PEI were used as dispersants, and Methyl Cellulose (MC) was used as the rheology modifier. The different factors include changing the solid loading of Si3N4, varying concentration of dispersants used as well as the adding of rheology modifier. All of which will have an effect on the viscosity of the ‘inks’, and its ability to be used in 3D printing. There were 3 experimental set-ups conducted to discover the optimal concentrations of solid loading, dispersant and rheology modifier as well as its effects when varied. A Rheometer was used as the main measurement tool for all 3 experiments, in order to record the measured viscosity. Potential ‘inks’ were highlighted. Lastly, the potential ‘inks’ are extruded via syringe to determine its ability to be 3D printed. Archimedes’ principle was used to measure the density of the sintered samples, while SEM allows for observation of porosity. The solid loading was able to reach as high as 62% when mixed with 1% PEI. Optimal shear thinning behavior was observed at 4% PAA and 4% PEI, and its potential to be used in 3D printing highlighted. The addition of Methyl Cellulose resulted in better and more prominent shear thinning behavior, where its ability to be used in 3D printing is higher. Furthermore, it is important to highlight the successfulness of 62% Solid loading, 4% PEI, 1% MC, though syringe testing. Thus, this indicating the mixture’s ability to be 3D printed.